Kenyamanan Antropometri Kursi Jemaat pada Bangunan Cagar Budaya Gereja Pandu, Kota Bandung - Yemima Fatilinia Gea; Moh. Rizky Taufik Hidayat; Muhamad Ridwan Nasir; Muhammad Fathur Abinaya (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2023)
Title: Convenience of Anthropometric Church of The Church at The Cultural Reserve Building of Pandu Church, Bandung City Anthropometry greatly influences comfort, especially for the Catholic Church of the Seven Sorrows Parish (Pandu Church) users in Bandung City as a place of worship. One of the most fundamental components of worship in a church is the need for church pews that conform to the anthropometric standards of its users. This study explores the comfort of using church pews in the Pandu Church of Bandung City. The research method employed is qualitative descriptive, involving data collection through sampling, research studies, and relevant literature searches related to the study object, as well as several stages according to the field implementation mechanism to obtain existing data and documentation. The analysis results show size, distance, and length differences between the two variations of church pews in the Pandu Church.